The Analysis of Damages and Remedies In Environmental Law: Case Study of PT. Kallista Alam - Miftahur Rahmah; Nurleli; Sahrizal; Riski Anggara; Muhammad Hatta (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
One of the important events in environmental law enforcement in Indonesia is the case of PT. Kallista Alam about theburning of peatland in Rawa Tripa, Aceh. Based on the decision of the Meulaboh District Court No. 12/PDT. G/2012/PN.MBO, which was later strengthened by the Banda Aceh High Court and the Supreme Court, the purpose of this study is toexamine aspects of compensation and environmental restoration. The research uses juridical-normative methods, using theanalysis of court decisions. The results of the analysis show that, based on Article 88 of Law No. 32 of 2009, the courtapplies the principle of strict responsibility, which establishes responsibility without proof of error. PT. Kallista Alam wassubject to compensation and recovery of IDR 366 billion, including ecological losses and active recovery. However, manychallenges hinder the implementation of the decision. This includes constant legal remedies and inadequate oversight ofexecutions. Concerning the principles of ecological justice and sustainable development, this decision relies heavily oncooperation between judicial institutions, government, and civil society. Keywords: Environmental Law, Strict Liability, Compensation, Ecological Recovery, Sustainable Development.